KARAKTERISASICYMBIDIUM MOSAIC VIRUS (CYMMV) PADA TANAMAN ANGGREK - KHALIMI, KHAMDAN; SIADI, KETUT (Agrotrop : Journal on Agriculture Science, 2012)
Characterization ofCymbidium mosaic virus (CymMV) on Orchid Plant Orchids are affected by more virus disease problems than most crops, reducing their commercial values considerably. Orchid viruses are widespread in cultivated orchids, withCymbidium mosaic potexvirus (CymMV) being the most prevalent. CymMV high incidence in cultivated orchids has been attributed to the stability and ease of transmission of this virus through cultural practices. CymMV induces floral and foliar necrosis. The virus also reduce plant vigor and lower flower quality, which affect their economic value. The objective of the research is to characterize the virus causing mosaic or chlorotic and necrotic on orchids in West Java. A reverse transcription-polymerase chain reaction (RT- PCR) assays using oligonucleotide primers specific to CymMV were also successfully amplified the regions of the coat protein (CP) gene of the virus. Analysis by using sodium dodecyl sulphate- polyacrylamide gel electrophoresis (SDS-PAGE) revealed that the virus have a major structural protein with an estimated molecular weight of 28 kDa. Aligments of partial nucleotide sequences of the CP gene displayed 86 to 92% homology to CymMV isolates from other countries.
Keywords: CymMV,orchids